Effect of feeding whole cottonseed as a supplement on digestibility and rumen fermentation characteristics of sheep (Bangladesh Journal of Animal Science, 2018)
An experiment was conducted in vivo to investigate the effects on the apparent feed digestibility and rumen fermentation of feeding whole cottonseed (WCS) as a supplement for sheep fed grass hay (GH). Four different diets (T1, T2, T3 and T4) were used as GH alone, GH plus 150, 300 and 500 g WCS d-1 on fresh basis. The main objectives of the in vivo experiment were to examine digestibility and rumen fermentation characteristics (pH, ammonia and VFA concentration) of sheep fed four diets. The results of this experiment indicated that supplementation of WCS at a level of 500 g d-1 (0.37 of the diet) with GH reduced DM, ADF and NDF digestibility. There was no statistically significant effect on total rumen VFA, but the molar proportions of acetate, propionate and butyrate were altered by the addition of highest rate of WCS. These results suggested that WCS might have reduced the number or activity of cellulolytic rumen microorganisms.Bang. J. Anim. Sci. 2017. 46 (4): 239-243